The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1149/2.0811503jes
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of PDDA Functionalized Reduced Graphene Oxide Decorated with Gold Nanoparticles and Its Electrochemical Response toward Levofloxacin

Abstract: In this work synthesis of water-dispersible reduced graphene oxide (rGO), decorated with gold nanoparticles (AuNPs), was carried out in the presence of poly(diallyldimethylammonium chloride) solution (PDDA). The as-prepared hybrid nanocomposite (Au/PDDA/rGO) was characterized using various surface, structural, and electrochemical analysis techniques, such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and voltammetry. The electrochemical performance of Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…23 Poly(diallyldimethylammonium chloride), PDDA, is a linear cationic polyelectrolyte that has been reported to be attractive for the surface functionalization of a nanomaterial. 24 It can also act as a stabilizer, disperser and linker in a nanocomposite. 25 Its positive surface charge can provide additional active sites and enable electrostatic attraction for the adsorption of an analyte.…”
Section: Introductionmentioning
confidence: 99%
“…23 Poly(diallyldimethylammonium chloride), PDDA, is a linear cationic polyelectrolyte that has been reported to be attractive for the surface functionalization of a nanomaterial. 24 It can also act as a stabilizer, disperser and linker in a nanocomposite. 25 Its positive surface charge can provide additional active sites and enable electrostatic attraction for the adsorption of an analyte.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these advantages, conventional electrodes used in electrochemical measurements have poor performance due to the easy fouling of their surfaces by the analyte and the intermediate products formed by the electrode reaction. For this reason, the surfaces of carbon-based electrodes have been altered by utilizing a wide range of modifiers such as nanostructured noble metals [18] and metal oxides, [11,19] carbon-based nanomaterials such as graphene (GR), [20] graphene oxide (GO), [4,6,21,22] carbon nanotube (CNT) [23] and conductive polymers [2,5,20,24] for selective and sensitive LEV detection. Conductive polymers are one of the most frequently used modifiers due to their homogeneity, repeatability, good stability, and strong adhesion to the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, a growing number of studies have shown successful applications of PDDA in other areas. It can be a functional, reducing and stabilizing agent in the preparation of graphene based composites for use in highly selective electrochemical sensors for various substances, such as esculetin [1], 4-chlorophenol [2], paracetamol, and diclofenac [3], β-nicotinamide adenine dinucleotide [4] and levofloxacin [5]. PDDA is used as a dispersive agent to obtain supermagnetic Fe3O4/PDDA nanocomposites [6].…”
Section: Introductionmentioning
confidence: 99%